Health promoting schools in Latin America: A review of the period 1996-2009 - Carmelinda Monteiro Costa Afonso; Maria de Fátima Lobato Tavares; Vera Lúcia Luiza (Universidade de Fortaleza, 2013)
Objective: To identify and discuss the scientific production on Health-Promoting Schools in Latin America published in indexed databases, by understanding the scope of the health education initiatives reported in the programs or interventions. Methods: This was a scientific literature review study, performed in LILACS, MEDLINE and SCOPUS databases, using as the main search term 'Health Promoting School', followed by 'Latin America'. It covered the period from 1996 to 2009, situating the start point ten years after the publication of the Ottawa Charter and one year after the official launch of the Health-Promoting Schools Regional Initiative (Iniciativa Regional de Escolas Promotoras de Saúde - IREPS) by the Pan-American Health Organization (PAHO). Inclusion criteria were defined, articles were retrieved in English, Portuguese and Spanish, and data was processed in three arrays of analysis. Results: The application of search keys led to 2,429 documents, reduced to 28 after applying the filter for Latin America, on which the inclusion criteria were applied, resulting in eight articles. Most of them stressed the importance of effectiveness studies, and half focused on the reduction of some specific morbidity, without prioritization of the conceptual axes contained in the Ottawa Charter. Conclusion: The publications addressed mainly the effectiveness of the interventions, conceptual coherence between the interventions and the health promotion principles, and the education process of the actors involved. Qualitative approaches, including documentary analysis, semi-structured interviews, focal group and participant observation, were the predominant methodological procedures. Intersectorial coordination was pointed out as the main strategy for sustainability of the experiences.